(untitled) (UNED Research Journal, 2016)
In 1938, the American multinational United Fruit Company built a small city in Golfito, South Pacific of Costa Rica. Golfito persists today as an urban area flanked by a mountain chain and a small bay surrounded by mangroves. We applied a set of environmental indicators to assess the current environmental quality of the landscape. We compared 106 photographs of Golfito with photographs from San José (capital of Costa Rica) as a reference; this comparison found a smaller proportion of urban green areas, but more trees and forest in Golfito. Contemporary architecture and public spaces have few facilities (such as sidewalks, public lighting and furnishing), and suffers from deterioration and low adaptation to tropical climatic conditions, especially in traditional architectural remains. Landscape management must make the natural components compatible with the cultural components, and Golfito is unique in the country because of its intense and fragile relationship among city, history and nature. We recommend priority conservation in risk management, public space comfort, valorization of the built heritage and abandoned areas, and an increase of urban green areas.